2013
DOI: 10.1159/000355491
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Coaxial Microincision Cataract Surgery for Uveitis-Associated Cataract without Postoperative Systemic Steroid Therapy

Abstract: Purpose: To study the necessity of prophylactic systemic steroid therapy after coaxial microincision cataract surgery (MICS) conducted in aged patients during remission of uveitis. Procedures: A total of 17 consecutive patients who underwent MICS were enrolled in this retrospective study. The median age was 73 years. MICS via a 2.2-mm incision was performed. None of the patients received systemic steroid administration after surgery. The visual acuity, intraocular pressure (IOP) and inflammation scores were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…A study of 61 patients (72 eyes) followed up for ≥ 5 years (mean 91 months) showed that macular edema or scarring occurred in 17 eyes (24%), PCO occurred in 69 eyes (96%), and glaucoma drainage surgery was required up to the latest follow-up examination in 11 eyes (15%). [ 23 ] Recently, Takayama et al [ 24 ] reviewed 17 patients who underwent coaxial microincision cataract surgery and that postoperative complications were rare; elevated IOP and exacerbated uveitis occurred in 1 eye each.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 61 patients (72 eyes) followed up for ≥ 5 years (mean 91 months) showed that macular edema or scarring occurred in 17 eyes (24%), PCO occurred in 69 eyes (96%), and glaucoma drainage surgery was required up to the latest follow-up examination in 11 eyes (15%). [ 23 ] Recently, Takayama et al [ 24 ] reviewed 17 patients who underwent coaxial microincision cataract surgery and that postoperative complications were rare; elevated IOP and exacerbated uveitis occurred in 1 eye each.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Furthermore, Takayama et al reported that regional steroid therapy alone can control relapse of uveitis in older uveitis patients. 2 Systemic corticosteroids induce various systemic adverse effects such as hyperglycemia, hypertension, and osteoporosis. 27 Minimally invasive procedures performed during cataract surgery such as small-incision phacoemulsification are effective in obtaining satisfactory results with less frequent postoperative complications; 2 this suggests that prophylactic systemic corticosteroid therapy is not necessary before and after the minimally invasive cataract surgery, at least in most of older uveitis patients in whom the quiescence of intraocular inflammation had been achieved for at least 3 months before cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We set targets according to the outcomes of previous reports. 2 , 12 When we assumed improvement of visual acuity (logMAR) at 0.5±0.35 in the uveitis group 12 and 0.3±0.25 in the control group, 2 we estimated the number of the necessary eyes according to significant difference between the uveitis and the control group in Student’s t -test. However, it was difficult to enroll enough patients to reach the target numbers in the uveitis group because there were few patients with uveitis in whom cataract surgery alone was enough to improve their visual acuity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…В то же время в литературе до сих пор дискутируется вопрос о целесообразности имплантации в этих случаях интраокулярных линз (ИОЛ) -на определенном этапе развития факохирургии наличие осложненной увеальной катаракты считали относительным противопоказанием для интраокулярной коррекции афакии. На сегодняшний день большинство авторов считает возможным имплантацию ИОЛ при контролируемом течении увеита в период ремиссии под «прикрытием» противовоспалительной терапии в пред-и послеоперационном периоде, так как это существенно улучшает функциональные результаты вмешательств [8,[9][10][11][12][13].…”
unclassified